Efektivitas Metode Multisensoris dalam Penguasaan Fonem Bahasa Indonesia pada Siswa Sekolah Dasar - Feliana, Hana; Putri A, Intan Nova; Imaniar T, Gracia Zeeanya; Nisa, Alya Zahratun; Maufiroh, Siti; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the effectiveness of multisensory methods in improving Indonesian phoneme mastery in primary school students. This study uses a qualitative approach with a case study design conducted on first-grade students at SD Negeri 1 Sinduadi. The research subjects were selected purposively, considering the characteristics of students who are in the early stages of literacy. Data were collected through observation of student learning activities, interviews with teachers and students, and documentation of learning activities. All data were analysed using thematic analysis techniques to identify patterns of change in student behaviour and phoneme skills. The results of the study indicate that the multisensory method can significantly improve sensory engagement, learning motivation, and phoneme retention. Students find it easier to distinguish between similar phoneme sounds and demonstrate positive learning transfer outside the classroom. However, the application of this method requires teachers to be prepared in terms of preparing teaching aids and adjusting strategies to student characteristics. Overall, the multisensory method has proven to be effective and enjoyable in supporting basic literacy achievement in primary schools, so it is recommended that it be applied more widely with adequate resources and training for teachers.